Design and Fabrication of Cost-Effective Low-Speed Subsonic Open Type Wind Tunnel - Abdul Basit; Sufyan Ahmed; Muhammad Hamza; Sarmad Ali Shah; Samar Iqbal; Muhammad Hassan Razzaq; Sheharyar Malik (Pakistan Journal of Engineering & Technology, 2020)
This paper presents the design and manufacturing of open circuit low-speed wind tunnel. The design of the contraction cone, test section and diffuser are finalized by the numerical analysis performed on ANSYS CFD software. A unique insight into the design of the contraction cone is presented. A fifth-order polynomial is used to model the contraction cone in PRO-E software. It allowed designing the test section with minimum turbulence and flow serration and a flow velocity profile of 20 m/s. The cross-sectional area of the test section and diffuser are selected after analytical calculations. The diffuser is designed as such to avoid pressure loss by incorporation changes in the rectangular cross-section. The initial study performed on the design helped us to select the fan with suitable power. Moreover, the intake of the contraction cone is equipped with the honeycomb structure of facilitating the laminar flow into the contraction cone. Following on to the initial numerical analysis, the fabrication of the wind tunnel is performed. Besides, a separate lift/drag measuring force system is also prepared; the intuitive design is cost-effective as well as accurate. The placement of anemometer helped us to directly measure the test section velocity, which is found to be 17 m/s.